2004
DOI: 10.1090/conm/346/06284
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of the self map 𝑣⁹₂ on the Smith-Toda complex 𝑉(1) at the prime 3

Abstract: Let V (1) be the Smith-Toda complex at the prime 3. We prove that there exists a map v 9 2 : Σ 144 V (1) → V (1) that is a K(2) equivalence. This map is used to construct various v 2 -periodic infinite families in the 3-primary stable homotopy groups of spheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In [8], we proved the 'only if' part. For the survivors, we have β s for s > 0 with s ≡ 0, 1, 2, 5, 6 mod 9 by M. Behrens and S. Pemmaraju [1].…”
Section: Introduction and Statements Of Resultsmentioning
confidence: 99%
“…In [8], we proved the 'only if' part. For the survivors, we have β s for s > 0 with s ≡ 0, 1, 2, 5, 6 mod 9 by M. Behrens and S. Pemmaraju [1].…”
Section: Introduction and Statements Of Resultsmentioning
confidence: 99%
“…The identity map V (1) → V (1) does have order 3. By [6], V (1) has a v 9 2 -self map, and hence L K(2) V (1) is 144-periodic. In [12] we showed that the homotopy groups of L K(2) V (1) are exactly 144-periodic; see…”
Section: The Duality Theoremmentioning
confidence: 99%
“…The identity map V (1) → V (1) does have order 3. By [BP04], V (1) has a v 9 2 -self map, and hence L K(2) V (1) is 144-periodic. In [GHM04] we showed that the homotopy groups of L K(2) V (1) are exactly 144-periodic; see also the charts at the end of [GH16].…”
Section: The Duality Theoremmentioning
confidence: 99%